Analisis Kriteria Pemilihan Pemenang TenderKontaktor Konstruksi di DKI Jakarta - Ricky Rinaldi; Mardiaman Mardiaman (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2020)
AbstractIn Indonesia, the process of selecting public service sector contractors is regulated in Presidential Decree No. 16 of 2018.Â  It seems fairly complete selection methods, but theapplication still has several weak points.Due to the ability of evaluations which are very limitedand based on the lowest bid evaluation system only, it doesnâ€™t get optimum results in terms oftime, quality, and cost in the construction phase. Inexperienced and poor performancecontractors undertake most of the projects established by this selection method. As analternative, the application of value-based evaluation methods (scoring) is a challenge in publicservice sector projects in DKI Jakarta. To overcome this problem, the research uses AnalyticalHierarchy Process and sensitivity analysis tools to determine criteria, sub-criteria, and weightsas input for refining the selection of tender winners. The results of data processing showed thathe criteria for the financial capability that had the most impact, 44.9% small scale companies, 39.3% medium scale companies, and 45.4% large scale companies. The lowest weight in largescale companies is in the HSE policy criteria at 10.2%, meanwhile, the lowest weight in smaland medium scale companies is company experiences criteria with 12.0% and 13.1%respectively. Some differences found that the dominant criteria and the most sensitive criteria, iis the implication of this study for tender criteria selection. Furthermore, the composition ocriteria and sub-criteria based on each company's scale would have to re-evaluate by the government as the policymaker on public service construction projects. Therefore, companies will also make some adjustments to the policies.